Summer Olympic Games hosting infrastructure requirements: still too big for most of the world? - Griesbach, J. W. (University of Peloponnese, 2021)
The Summer Olympic Games are currently only being awarded to global giant cities, with Tokyo, Paris, and Los Angeles slated to host the next three Summer Games. This study aims to examine why global giant cities are currently the only type of city hosting the Games. Furthermore, it aims to define and create an understanding of how another type of city, the mid-tier city, will be able to again host the Games in the future as they have in the past, in cities such as Barcelona, Sydney, and Athens. The literature shows that a history of gigantism and scandals has forced the IOC to the point where it had little choice but to choose only global giant cities because of failed public referenda and intense media scrutiny. Additional research conducted amongst a select group of Olympic experts found that there is a strong belief mid tier cities will once again be hosts of the Games, and that the future of the Olympic Games is bright thanks to the changes outlined in Agenda 2020 and The New Norm. The project concludes with recommendations for the IOC to go even further in its reforms to guarantee that Olympic ideals and Olympism are central to everything the IOC does, improving the reach and impact of the Olympic Movement and allowing mid-tier cities to once again be part of the narrative about hosting the Summer Olympic Games.